PELATIHAN DAN SOSIALISASI UJI SKEMA SERTIFIKASI KOMPETENSI BISNIS DIGITAL SEBAGAI SARANA PENINGKATAN KOMPETENSI DI UNAS - Muhaemin Muhaemin; Firdaus, Mohamad; Imam Himawan, Imam Himawan (CV. Denasya Smart Publisher, 2024)
This community service activity aims to enhance the competencies of students and lecture at Universitas Nasional (UNAS) in the field of digital business through training and socialization of the competency certification scheme. Digital business competency certification has become essential in the digital era, when these skills are needed to improve the quality of human resources and the competitiveness of graduates. The methods used in this activity include training, competency test simulations, and the socialization of the benefits of certification in the job market. Evaluation results show that this activity successfully increased participants' understanding of the certification process and their readiness to undertake the competency tests. It is hoped that, through this activity, UNAS graduates will gain superior competencies in the digital business field.